Acute psoriatric arthropathy precipitated by oxprenolol. Issue 1 (February 1984) - Macfarlane, D G; Settas, L
Abstract : A previously normal 58-year-old woman developed a widespread psoriatic rash and asymmetrical peripheral polyarthritis a week after beginning treatment with oxprenolol for hypertension. Skin and joint disease resolved simultaneously after drug withdrawal and have not recurred.